Effect of the A30P mutation on the structural dynamics of micelle-bound alpha synuclein released in water: a molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (European Biophysics Journal With Biophysics Letters, 2012)
Atomistic molecular dynamics simulation has been used to probe the effect of the A30P mutation on the structural dynamics of micelle-bound, helical alpha Synuclein when released in an aqueous environment. On the timescales simulated, the effect of the mutation on the secondary structure is restricted to local changes close to the mutation site in the N-terminal helical domain. The changes are transient, and all residues except Lys23 recover their initial structure. The local behavior due to the mutation gives rise to a global difference in the A30P mutant in the form of a permanent kink in the N-terminal helical domain.
Keywords: A30P mutation; Alpha synuclein; Kink formation; molecular dynamics simulation; Structural persistence

Cross dimerization of amyloid-beta and alpha synuclein proteins in aqueous environment: a molecular dynamics simulations study - Jose, Jaya C.; Chatterjee, Prathit; Sengupta, Neelanjana (Plos One, 2014)
Self-assembly of the intrinsically unstructured proteins, amyloid beta (A beta) and alpha synclein (alpha Syn), are associated with Alzheimer's Disease, and Parkinson's and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between A beta and alpha Syn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontaneous interactions between these two sequentially dissimilar proteins and key characteristics of the resulting cross complexes. In this study, we have used atomistic molecular dynamics simulations to probe the possibility of cross dimerization between alpha Syn(1-95) and A beta(1-42), and thereby gain insights into their plausible early assembly pathways in aqueous environment. Our analyses indicate a strong probability of association between the two sequences, with inter-protein attractive electrostatic interactions playing dominant roles. Principal component analysis revealed significant heterogeneity in the strength and nature of the associations in the key interaction modes. In most, the interactions of repeating Lys residues, mainly in the imperfect repeats `KTKEGV' present in alpha Syn(1-95) were found to be essential for cross interactions and formation of inter-protein salt bridges. Additionally, a hydrophobicity driven interaction mode devoid of salt bridges, where the non-amyloid component (NAC) region of alpha Syn(1-95) came in contact with the hydrophobic core of A beta(1-42) was observed. The existence of such hetero complexes, and therefore hetero assembly pathways may lead to polymorphic aggregates with variations in pathological attributes. Our results provide a perspective on development of therapeutic strategies for preventing pathogenic interactions between these proteins.

Non-uniform early structural response of globular proteins to cold denaturing conditions: a case study with Yfh1 - Chatterjee, Prathit; Bagchi, Sayan; Sengupta, Neelanjana (Journal of Chemical Physics, 2014)
The mechanism of cold denaturation in proteins is often incompletely understood due to limitations in accessing the denatured states at extremely low temperatures. Using atomistic molecular dynamics simulations, we have compared early (nanosecond timescale) structural and solvation properties of yeast frataxin (Yfh1) at its temperature of maximum stability, 292 K (T-s), and the experimentally observed temperature of complete unfolding, 268 K (T-c). Within the simulated timescales, discernible ``global'' level structural loss at T-c is correlated with a distinct increase in surface hydration. However, the hydration and the unfolding events do not occur uniformly over the entire protein surface, but are sensitive to local structural propensity and hydrophobicity. Calculated infrared absorption spectra in the amide-I region of the whole protein show a distinct red shift at T-c in comparison to T-s. Domain specific calculations of IR spectra indicate that the red shift primarily arises from the beta strands. This is commensurate with a marked increase in solvent accessible surface area per residue for the beta-sheets at T-c. Detailed analyses of structure and dynamics of hydration water around the hydrophobic residues of the beta-sheets show a more bulk water like behavior at T-c due to preferential disruption of the hydrophobic effects around these domains. Our results indicate that in this protein, the surface exposed beta-sheet domains are more susceptible to cold denaturing conditions, in qualitative agreement with solution NMR experimental results. (C) 2014 AIP Publishing LLC.

Cloning, expression and in silico studies of a serine protease from a marine actinomycete (Nocardiopsis sp NCIM 5124) - Rohamare, Sonali; Gaikwad, Sushama M.; Jones, Dafydd; Bhavnani, Varsha; Pal, Jayanta; Sharma, Ranu; Chatterjee, Prathit (Process Biochemistry, 2015)
A serine protease (N. protease), from Nocardiopsis sp., was cloned and expressed in Escherichia coli and investigated for its potential kinetic stability. Protein expression using two vectors, pET-22b (+) and pET-39b (+) was compared based on proper folding and soluble expression of the protein. pET-39b (+) was found to be a better vector for soluble expression of this protease containing disulfide bonds. In silico studies were also carried out for N. protease. Homology modeling suggested N. protease to be a member of PA clan of proteases. The phylogenetic analysis showed relatedness of N. protease to kinetically stable proteases. Molecular docking studies performed exhibited interaction of a peptide substrate with catalytic pocket of the enzyme. High temperature MD simulations were performed on N. protease to study its unfolding behavior and comparisons were made with alpha LP. A novel approach to study `cooperativity' of protein unfolding was undertaken, wherein `P' value analysis based on phi and psi values of the protein was performed. Data showed sharper P value transition for alpha LP when compared to N. protease thus indicating relatively less kinetic stability of N. protease. Present study holds significance as the non-streptomycete actinomycetes group is least explored and ensures industrially important enzymes with exceptional stabilities. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Actinomycetes; Cloning and expression; Kinetic stability; Protease; Thermal simulation

Signatures of protein thermal denaturation and local hydrophobicity in domain specific hydration behavior: a comparative molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (Molecular Biosystems, 2016)
We investigate, using atomistic molecular dynamics simulations, the association of surface hydration accompanying local unfolding in the mesophilic protein Yfh1 under a series of thermal conditions spanning its cold and heat denaturation temperatures. The results are benchmarked against the thermally stable protein, Ubq, and behavior at the maximum stability temperature. Local unfolding in Yfh1, predominantly in the beta sheet regions, is in qualitative agreement with recent solution NMR studies; the corresponding Ubq unfolding is not observed. Interestingly, all domains, except for the beta sheet domains of Yfh1, show increased effective surface hydrophobicity with increase in temperature, as reflected by the density fluctuations of the hydration layer. Velocity autocorrelation functions (VACF) of oxygen atoms of water within the hydration layers and the corresponding vibrational density of states (VDOS) are used to characterize alteration in dynamical behavior accompanying the temperature dependent local unfolding. Enhanced caging effects accompanying transverse oscillations of the water molecules are found to occur with the increase in temperature preferentially for the beta sheet domains of Yfh1. Helical domains of both proteins exhibit similar trends in VDOS with changes in temperature. This work demonstrates the existence of key signatures of the local onset of protein thermal denaturation in solvent dynamical behavior.

Mechanistic principles of antimicrobial peptides uncovered by charge density-based machine learning - Malshikare, Hrushikesh; Priyakumar, U. Deva; Chatterjee, Prathit; Sengupta, Durba (Chemical Communications, 2026)
Antimicrobial peptides (AMPs) are emerging as potent alternatives to conventional antibiotics, yet their diverse nature due to divergent mechanisms of action hinders rational design. Here, we present an electrostatics-stratified computational framework that uncovers key physicochemical principles governing AMP activity. Experimentally validated peptides were grouped by average charge per residue (i.e., the charge/length of the peptide) and analyzed through integrated sequence-, structure-, and chemistry-based descriptors. Distinct molecular signatures emerged across electrostatic regimes: low-charge/length peptides rely on amphipathic organization via structural compactness, whereas the intermediate-charge/length peptides exhibit balanced hydrophobicity and electrostatics. The high-charge peptides couple strong cationic attraction with lipophilicity and tryptophan anchoring to mainly disrupt membranes. Interestingly, hydrophobic moment, which is a measure of the amphipathicity, is found to be important in all three classes of AMPs. This study identifies distinguishing features of AMP sub-groups and suggests design guidelines for developing selective and potent next-generation AMPs.